Reuse of a raw rice husk substrate after tomato cultivation for the production of pickling cucumber hybrids (Cucumis sativus L.) in a leachate recirculation system (2018)
The objective of this study was to evaluate the growth and yield of three pickling cucumber hybrid cultivars: Feisty, Kybria and Tony, using a fresh rice husk substrate and a rice husk substrate reused after tomato cultivation in a leachate recirculation system (CAR). This trial was installed in a greenhouse located in southern Brazil between October, 2016 and January, 2017. The following variables were evaluated: dry mass of leaves, stems and fruits, number of leaves, leaf area index and yield. No significant interactions were found between the cultivars and the substrates. The reused substrate did not affect the growth nor the yield of the plants; however, the CAR caused an increase in the average weight of the cucumber fruits and a decrease in the number of harvested fruits. 'Kybria', followed by 'Tony', presented a higher fruit growth and yield than 'Feisty', in which a greater vegetative growth was observed to the detriment of the fruit growth. The yields were high with values of 8.33, 7.18 and 4.85 kg m-2, respectively, for the hybrids: Feisty, Kybria and Tony. In conclusion, rice husks, new and reused, are excellent for the production of canned cucumbers in a nutrient recirculation system.